Analisis Produksi Serasah Mangrove pada Hutan Mangrove Desa Kurau Timur, Kabupaten Bangka Tengah, Bangka Belitung: Analysis Production of Mangrove Litter in the Mangrove Forest of Kurau Timur Village, Central Bangka Regency, Bangka Belitung - Randiansyah Randiansyah; Henri Henri; Arthur Muhammad Farhaby (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Mangrove forests have many ecological functions such as retaining and trapping sediments, dampening waves, providing protection for fish and other biota, and assimilating nutrients. Most of the nutrients returned to the forest floor are in the form of litter. Litter has an important role for the soil and the microorganisms in it. This study aims to measure the productivity of mangrove litter in the mangrove forest of Kurau Timur Village, Central Bangka Regency, Bangka Belitung. The method used to measure litter production is litter storage using a 1m x 1m litter trap with litter collection every 7 days for 3 months. Environmental parameter data analysis was performed by PCA (Principal Component Analysis). The rate of litter production in the mangrove forest of East Kurau Village is with a dry weight of 2.72 gr/m2/day. The components that make up litter are grouped into 3 components, namely leaves (66%), stems (18%), and flowers/fruits (16%). The litter layer on the mangrove forest floor of Kurau Timur Village is with an average dry weight of 69.02 grams, a water content of 40.73%, and an estimated average biomass of 3.08 tons/ha.